Ronald Harmon Brown papers - Brown, Ronald Harmon, 1941-1996.
Speeches, reports, briefing books, government documents, topical files, trip itineraries, newsletters, printed matter, newspaper clippings, photographs, and other papers relating to Brown's service as U.S. secretary of commerce during President Bill Clinton's administration. Documents his effort to expand American exports, the National Information Infrastructure Advisory Council (U.S.), agencies of the Department of Commerce such as the National Institute of Standards and Technology (U.S.) and the U.S. National Oceanic and Atmospheric Administration, congressional relations including legislation to dismantle the Department of Commerce, and his domestic and international trips and missions.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
U.S. secretary of commerce and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Clinton, Bill, -- 1946-; United States. -- Department of Commerce; United States. -- National Oceanic and Atmospheric Administration; National Information Infrastructure Advisory Council (U.S.); National Institute of Standards and Technology (U.S.); Executive departments -- United States -- Reorganization; Exports -- United States; Foreign trade promotion -- United States; Information networks -- United States; Science and state -- United States; Technology and state -- United States; Telecommunication -- United States; United States -- Commerce; United States -- Commercial policy; United States -- Economic policy -- 20th century; United States -- Foreign economic relations; Cabinet officers; Lawyers